Reliability of bilateral and shear components in a two-legged counter-movement jump - Gordon, D.; Hayward, S.; van Lopik, K.; Philpott, L.; West, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
Strength asymmetry can be detrimental to athlete performance and may lead to injury. The countermovement jump (CMJ) can be used to measure strength asymmetry via shear force production. The reliability of parameters and effects of asymmetry and shear force production on vertical CMJ performance were evaluated in a study with 15 university-level sprint and high jump athletes (m = 11, f = 4). The athletes performed three CMJs on two occasions, separated by 1 week. Tri-axial ground reaction force (GRF) was recorded using two force platforms embedded within a bespoke weight training area. Key performance metrics were calculated in real-time describing total CMJ performance, asymmetry and shear force production. Changes in the means and coefficients of variation (CV) were used to express reliability. Twenty-six parameters from the Total analysis and 21 Asymmetry analysis parameters showed a CV lower than 10%. Temporal and kinetic variables describing Asymmetry analysis highlight a lower CV compared with equivalent parameters derived from Total analysis. Shear parameters show high levels of CV compared with Total analysis and Asymmetry analysis. The measures of asymmetry calculated using methods described in this work were shown to be reliable for monitoring CMJ performance. No significant negative relationships were found between measures of asymmetry or shear force and traditional performance metrics in the CMJ (e.g. jump height, specific peak power and peak force). Further work is required to identify the potential of reducing asymmetry on CMJ performance.